2010
DOI: 10.1109/jsac.2010.100421
|View full text |Cite
|
Sign up to set email alerts
|

Distortion optimal transmission of multi-layered FGS video over wireless channels

Abstract: Abstract-We identify an analytical expression for the distortion of a scalable video bitstream containing a Base Layer (BL) and one or more Enhancement Layer (EL) bitstreams. Considering the different priority of BL and EL, we adopt our distortion expression for each of these bitstreams separately. Utilizing these distortion models, we propose a pair of low complexity Unequal Error Protection (UEP) methods for transmitting these bitstreams over a tandem channel. These onedimensional Forward Error Correction (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The design of our scheme is motivated by the observation that the error correction settings at MAC layer can be optimised in such a way that the overall packet losses caused by either link erasure or link overflow are minimised. As in [6], this paper uses RS codes with the interleaving technique shown in Fig. 3.…”
Section: Error Protection-level Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The design of our scheme is motivated by the observation that the error correction settings at MAC layer can be optimised in such a way that the overall packet losses caused by either link erasure or link overflow are minimised. As in [6], this paper uses RS codes with the interleaving technique shown in Fig. 3.…”
Section: Error Protection-level Analysismentioning
confidence: 99%
“…In error-prone wireless environments, a single bit error of the compressed video data may cause severe degradation in video quality. Therefore, channel coding techniques, such as automatic repeat request (ARQ) [5], forward error correction (FEC) [6], and hybrid schemes [7] are adopted to combat packet losses. Recent comparisons between ARQ and FEC revealed that for certain FEC block codes, the ARQ schemes increased both energy consumption and end-to-end latency [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a priority index was developed in [3,4] to indicate the priority that can be used for UEP. UEP has been considered in video transmission systems, as in [5][6][7][8][9][10][11][12][13][14][15]. In [5][6][7], an application layer resource type, such as parity data, was considered.…”
Section: Introductionmentioning
confidence: 99%
“…UEP has been considered in video transmission systems, as in [5][6][7][8][9][10][11][12][13][14][15]. In [5][6][7], an application layer resource type, such as parity data, was considered. In contrast, the studies [8][9][10][11][12][13][14][15] considered physical layer (PHY) optimization for SVC or MGS video streams, as in the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…While several schemes for video streaming over wireless channels have been introduced in the literature [14][15][16][17][18][19][20], the bulk of these scheme aim at the optimization of the performance of the source and/or channel encoders, with little to no considerations of the networking aspects. Many of these studies are concerned with the optimization of the effective throughput of the channel, without considering the impact of source and channel coding on the transport delay and delay jitter.…”
Section: Introductionmentioning
confidence: 99%